2002
DOI: 10.1002/cta.199
|View full text |Cite
|
Sign up to set email alerts
|

Optimal path finding with space‐ and time‐variant metric weights via multi‐layer CNN

Abstract: SUMMARYAnalogic CNN-based optimal path-ÿnding algorithm is proposed to solve the problem with spaceand time-variant metric weights. The algorithm is based on the analog version of modiÿed dynamic programming which is associated with non-linear templates and multi-layer CNN employing the distance computing (DC), the intermediate (I), and the path-ÿnding (PF) layers. The cell outputs of I layer are jointly utilized among the cells on the DC layer and the PF layers, which allows the network structure to be compac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…By applying relation (11) to all the pixels from the robot neighborhood, the template elements for path.tem must satisfy an inequality system. For the pixel, that represents the future position, the inequality is given by the relation (12) and for the other pixels by the relation (13).…”
Section: Template Design For Path Planning Of a Mobile Robotmentioning
confidence: 99%
“…By applying relation (11) to all the pixels from the robot neighborhood, the template elements for path.tem must satisfy an inequality system. For the pixel, that represents the future position, the inequality is given by the relation (12) and for the other pixels by the relation (13).…”
Section: Template Design For Path Planning Of a Mobile Robotmentioning
confidence: 99%
“…However, this method was not fully based on a CNN, since a CNN is only used as the first layer to produce the local currents of edges. Kim et al (2002) reported a multi-layer CNN to find the optimal path. In this study, the neural connections are symmetric and only a static environment is discussed without any discussions on a changing environment.…”
Section: Related Workmentioning
confidence: 99%
“…Our method is a global algorithm to compute the optimal light trace through taking the local minimum operation at each node. It is also an efficient solution when implemented with parallel processing of locally connected cells such as Cellular Neural Networks (CNN) [13]. This paper is organized as follows: Sect.…”
Section: Introductionmentioning
confidence: 99%